IMPLEMENTASI PERATURAN MENTERI PENDIDIKAN DAN KEBUDAYAAN NOMOR 5 TAHUN 2012 TENTANG SERTIFIKASI BAGI GURU DALAM JABATAN DI SMA NEGERI 5 SEMARANG - Sehpemita Christin Br Ginting; Aloysius Rengga (Journal of Public Policy and Management Review, 2018)
The focus of this study is about the implementation of Ministerial Regulations Of Educationand Culture Number 5 Year 2012 About Certification For Teacher In Position At Semarang 5th State Senior High School and about restricting factors. This research using theory from George Edward III with qualitative approach. Data were obtained from respondent and document. Coleccting data techniques were interview, dan documentation. Informant selecting uses purposive and snowball sampling. The research shows that Implementation of Ministerial Regulations Of Educationand Culture Number 5 Year 2012 About Certification For Teacher In Position At Semarang 5th State Senior High School already implemented according to the rules. Certification implementing by portofolio pattern, education and professional practice of teachers, and certification directly. In this study also found supporting and restricting factors. Restricting factor is information that not clear and inconsistent while supporting factors i.e. resources, dispotition, and bureaucratic structure, while. Recommendations that can be given is the education office provides clear information during the socialization and to motivate teacher to take certification, to minimize information inconsistency.